Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/2014jc010473
|View full text |Cite
|
Sign up to set email alerts
|

The “winter predictability barrier” for IOD events and its error growth dynamics: Results from a fully coupled GCM

Abstract: Within the Geophysical Fluid Dynamics Laboratory Climate Model version 2p1 (GFDL CM2p1) coupled model, we find that the winter predictability barrier (WPB) exists in both the growing and decaying phases of positive Indian Ocean dipole (IOD) events, due to the effects of initial errors. The physical mechanism of the WPB, in which the initial errors show a significant seasonal-dependent evolution with the fastest error growth in winter, is explored from the dynamical and thermodynamical viewpoints. In terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 64 publications
4
25
0
Order By: Relevance
“…The WPB for IOD predictions was reported by previous studies (Feng & Duan, ; Feng et al, ; Luo et al, ). Feng et al () showed that the seasonality of vertical temperature advection, latent heat flux, and shortwave radiation favor the season‐dependent evolution of prediction errors for IOD events.…”
Section: The Summer Predictability Barrier (Spb) Of Iod Events and Twsupporting
confidence: 70%
“…The WPB for IOD predictions was reported by previous studies (Feng & Duan, ; Feng et al, ; Luo et al, ). Feng et al () showed that the seasonality of vertical temperature advection, latent heat flux, and shortwave radiation favor the season‐dependent evolution of prediction errors for IOD events.…”
Section: The Summer Predictability Barrier (Spb) Of Iod Events and Twsupporting
confidence: 70%
“…Generally speaking, these additional observations would be assimilated by a data assimilation system to provide the numerical model a more reliable initial state. The idea of the target observation has been applied to some weather and climate events forecasting, such as Fronts and Atlantic Storm-Track Experiment (FASTEX; Synder 1996), North Pacific Experiment (NORPEX; Langland et al 1999), tropical cyclone (TC; Qin et al 2013;Qin and Mu 2012;Zhou and Mu 2011), Kuroshio large meander (KLM; Wang et al 2013), India Ocean Dipole (IOD; Feng et al 2014), ENSO Hu and Duan 2016), etc.…”
Section: The Target Observationmentioning
confidence: 99%
“…Recently, the nonlinear approach of CNOP has been successfully used to determine the sensitive areas for targeting in TC, IOD, KLM forecasting (Qin et al 2013;Qin and Mu 2012;Zhou and Mu 2011;Feng et al 2014;Wang et al 2013). For the TC forecasting, the CNOP is computed case by case and the sensitive areas for targeting observation are case dependent (Qin et al 2013;Qin and Mu 2012;Zhou and Mu 2011).…”
Section: The Target Observationmentioning
confidence: 99%
“…During the positive IOD events, strong negative subsurface temperature anomalies exist in the eastern Indian Ocean, with negative surface salinity anomalies in the central and eastern Indian Ocean, resulting in a large pressure gradient force to drive EUC during the August-November. Further, 2011;Ummenhofer et al 2009;Hashizume et al 2012;Feng et al 2014;Guo et al 2015;Yao et al 2016).…”
Section: Introductionmentioning
confidence: 99%